Plasma lipid metabolites associate with diabetic polyneuropathy in a cohort with type 2 diabetes. Issue 6 (6th May 2021) - Rumora, Amy E.; Guo, Kai; Alakwaa, Fadhl M.; Andersen, Signe T.; Reynolds, Evan L.; Jørgensen, Marit E.; Witte, Daniel R.; Tankisi, Hatice; Charles, Morten; Savelieff, Masha G.; Callaghan, Brian C.; Jensen, Troels S.; et al.
Abstract: Objective: The global rise in type 2 diabetes is associated with a concomitant increase in diabetic complications. Diabetic polyneuropathy is the most frequent type 2 diabetes complication and is associated with poor outcomes. The metabolic syndrome has emerged as a major risk factor for diabetic polyneuropathy; however, the metabolites associated with the metabolic syndrome that correlate with diabetic polyneuropathy are unknown. Methods: We conducted a global metabolomics analysis on plasma samples from a subcohort of participants from the Danish arm of Anglo‐Danish‐Dutch study of Intensive Treatment of Diabetes in Primary Care (ADDITION‐Denmark) with and without diabetic polyneuropathy versus lean control participants. Results: Compared to lean controls, type 2 diabetes participants had significantly higher HbA1c ( p = 0.0028), BMI ( p = 0.0004), and waist circumference ( p = 0.0001), but lower total cholesterol ( p = 0.0001). Out of 991 total metabolites, we identified 15 plasma metabolites that differed in type 2 diabetes participants by diabetic polyneuropathy status, including metabolites belonging to energy, lipid, and xenobiotic pathways, among others. Additionally, these metabolites correlated with alterations in plasma lipid metabolites in type 2 diabetes participants based on neuropathy status. Further evaluating all plasma lipid metabolites identified a shift in abundance, chain length, and saturation of free fatty acids in type 2 diabetes participants. Importantly, the presence of diabetic polyneuropathy impacted the abundance of plasma complex lipids, including acylcarnitines and sphingolipids. Interpretation: Our explorative study suggests that diabetic polyneuropathy in type 2 diabetes is associated with novel alterations in plasma metabolites related to lipid metabolism.